2017
DOI: 10.1115/1.4037578
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Air Injection and Cavity Size Within a Circumferential Combustor to Increase G-Load and Residence Time

Abstract: A gas turbine combustion process subjected to high levels of centrifugal acceleration has demonstrated the potential for increased flame speeds and shorter residence times. Ultracompact combustors (UCC) invoke the high-g phenomenon by introducing air and fuel into a circumferential cavity which is recessed radially outboard with respect to the primary axial core flow. Upstream air is directed tangentially into the combustion cavity to induce bulk circumferential swirl. Swirl velocities in the cavity produce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The minimum inner diameter was designed to be adaptable to the turbine stator of the original engine. By analyzing and summarizing previous studies, ,,, early HGCs were found to mainly consist of a main inlet, auxiliary inlet holes, and mixing guide vanes, making them relatively complex structures that cannot be easily integrated into micro turbojet engines. The new HGC structure is specific to the miniature turbojet engine, which creates a main combustion region based on the original annular flame cylinder combustion chamber so that the fuel is burned in a high- g environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum inner diameter was designed to be adaptable to the turbine stator of the original engine. By analyzing and summarizing previous studies, ,,, early HGCs were found to mainly consist of a main inlet, auxiliary inlet holes, and mixing guide vanes, making them relatively complex structures that cannot be easily integrated into micro turbojet engines. The new HGC structure is specific to the miniature turbojet engine, which creates a main combustion region based on the original annular flame cylinder combustion chamber so that the fuel is burned in a high- g environment.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the combustion efficiency was not significantly affected by different jet-air angles, the combustion efficiency was still approximately 99%, and the NOx emission decreased with an increase in gloading. Cottle et al 25 added a set of injection plates and baffles to an HGC with a diffuser to control the directions and ratios of the core and secondary streams. Subsequently, Bohan et al 26,27 designed a cooling scheme by designing holes to form a cooling film and hence mitigate the localized overheating problem of the HGC.…”
Section: Introductionmentioning
confidence: 99%